EKSISTENSI BUDAYA JAWA DI DESA BANGKO BAKTI KECAMATAN BANGKO PUSAKO KABUPATEN ROKAN HILIR - Abdullah '; Ridwan Melay; Bunari ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Existence is a word derived from the Latin is existere that have meaning: arise, arise, exist, and where they arise. Bangko Bakti is the village where the indigenous population is Malay, Javanese society first of all comes from the island of Java bertrasmigrasi to North Sumatra, then after the Java community who moved to North Sumatra kehidpan experiencing economic constraints. So then the Java community bertranmigrasi Bakti Bangko and residents of the Bangko Bakti. The reason they settled in Bangko Bakti is seen very good job opportunities in Bangko Bakti. The existence of Javanese culture in Desa Bakti Bangko Malay community for their willingness to use Java in the village culture Bangko Bakti, besides the similarities and liver kerendah two cultures that could Javanese culture well received by the Malay community in the village of Bangko Bakti. The strong influence of Javanese culture led to the Javanese cultural influence on the Malay community in Bakti Bangko. after affected Javanese, Malay community using a portion of Javanese culture in the everyday life of Malay culture in Bangko Bakti. Among them are: Language, some custom Java community did wages, art, food. While the Malay and Javanese cultural perceptions in people's lives Bangko Bakti notice of the existence of Javanese culture in Bangko Bakti, Behold, the two cultures portray the absence of a great good rejection of any society. When the Malay community culture using Java, the Java community does not feel disadvantaged. However, the Java community feel happy when Javanese is used by the Malay community in the village of Bangko Bakti.Keywords: Existence, Culture Java, Bangko Bakti.